Behavioral studies in healthy Standardbred trotters subjected to short term forced recumbency aiming at an adjunctive treatment in an acute attack of laminitis - Hansson, Elin (SLU/Dept. of Clinical Sciences (until 231231), 2011)
Laminitis is a debilitating disease causing much suffering to horses and ponies all over the world. It is manifested in the hooves as a mechanical failure of the suspensory apparatus between the hoof capsule and the distal phalanx. Due to the weight of the horse the disease may result in a dislocation of third phalanx.